ISOLASI DNA DAN AMPLIFIKASI FRAGMEN D-LOOP MITOKONDRIAL PADA IKAN Ompok hypophthalmus (Bleeker, 1846) DARI SUNGAI KAMPAR PROVINSI RIAU - Della Rinarta; Roza Elvyra; Dewi Indriyani Roslim (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Total DNA molecule and fragment of the mitochondrial D-loop region is needed to determine the nucleotides sequence of mitochondrial D-loop region from lais danau fish (Ompok hypophthalmus). Therefore, this study aimed to isolate and amplify mitochondrial D-loop region that can be used as genetic information resources of O. hypophthalmus. The samples of O. hypophthalmus were taken from flood plain river in Riau, Kampar River. Tail muscle of O. hypophthalmus was used for DNA isolation. DNA molecules were amplified using PCR machine with L15926 and H00651primers. The total DNA of O. hypophthalmus was obtained in this study. The amplification process produced 153 bp fragment mitochondrial D-loop region of O. hypophthalmus.